Upaya Perlindungan Anak terhadap Perkara Hadhanah - Anton Afrizal Candra (Jurnal HAM, 2022)
The hadhanah often lead to problems regarding law enforcement and the protection of children. The hadhanah case after being decided by the judge turned out to have no executive power when hadhin or hadhinah who had the obligationand responsibility to fulfill hadhanah financing could not implement it. This study aims to determine the efforts that can be made to protect children, especially against hadhanah problems from the perspective of Law Number 35 of 2014. The nature of this research is descriptive and the type of research is normative juridical, with a statutory approach and conceptual approach. Data collection was done by conducting literacy studies, and analyzing qualitatively. The results of the study found a form of legal protection for children as the executorial power against hadhanah case decision based on Law Number 35 of 2014.